The Horizon’s Hoop: Emerson’s “Monadnoc” in Contingency and History - Nicholas Birns (2014)
When it is spoken of at all, Emerson’s “Monadnoc” is described as a solicitation of natural sublimity. But a close rhetorical analysis of the poem reveals greater ambivalence about this sublimity than is apparent—linking it to later American philosophic poems by Frost, Stevens, Ammons, and Kinnell that at once solicit and question natural plenitude. Furthermore, “Monadnoc” is historically situated, both in terms of the issue of prior Indigenous habitation raised by the very Abenaki origin of its name and as instanced the comparisons to peoples in Western and Eastern Europe made by Emerson in addressing the community of people who live among the mountain. The trope of the horizon, it is argued, is deployed by the poem to link its natural and historical cognitive projects in an overall contingency, though it also operates to show how Emerson’s vision has been amended and elaborated by later, more explicitly cosmopolitan turnings. “Monadnoc” has been absent from the sustained historicist reconsideration of Emerson over the last thirty years; this essay argues that it should be central to further elaborations of this project and of Emerson’s contingent epistemology.